Echocardiographic functional determinants of survival in heart failure with abnormal ejection fraction - Ciampi, Quirino; Cortigiani, Lauro; Gaibazzi, Nicola; Rigo, Fausto; Zagatina, Angela; Wierzbowska-Drabik, Karina; Kasprzak, Jaroslaw D.; Djordjevic-Dikic, Ana; Haberka, Maciej; Barbieri, Andrea; Bartolacelli, Ylenia; Pepi, Mauro; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background and Aims. Patients with heart failure (HF) with reduced left ventricular (LV) ejection fraction (EF) have a heterogeneous prognosis, and assessment of coronary physiology with coronary flow velocity (CFV) and coronary flow velocity reserve (CFVR) may complement established predictors based on wall motion and EF.In a prospective multicenter study design, we enrolled 1,408 HF patients (age 66±12 years, 1,035 men), with EF <50%, 743 (53%) with coronary artery disease, and 665 (47%) with normal coronary arteries. Recruitment (years 2004-2022) involved 8 accredited laboratories, with inter-observer variability <10% for CFV measurement. Baseline CFV (abnormal value >31 cm/s) was obtained by pulsed-wave Doppler in mid-distal LAD. CFVR (abnormal value ≤2.0) was assessed with exercise (n=99), dobutamine (n=100), and vasodilator stress (dipyridamole in 1,149, adenosine in 60). Inducible myocardial ischemia was identified with wall motion score index (WMSI) stress> rest (cut-off ∆≥0.12). LV contractile reserve (CR) was identified with WMSI stress< rest (cutoff ∆≥0.25). Test response ranged from score 0 (EF>30%, CFV ≥32 cm/s, CFVR>2.0, LVCR present, ischemia absent) to score 5 (all steps abnormal). All-cause death was the only endpoint.Results. During a median follow-up of 990 days, 253 patients died. Independent predictors of death